Tanggung Jawab Direksi atas Terjadinya Pailit Perseroan Terbatas - Antonius Faebuadodo Gea; Hirsanuddin Hirsanuddin; Djumardin Djumardin (Journal of Education on Social Science (JESS), 2020)
This research was conducted to find out how the directors' accountability mechanism caused by an error or negligence caused the limited company to go bankrupt and how the legal consequences on the bankruptcy of a limited liability company. This type of research was classified as a normative legal research or also called doctrinal research, namely research that examined the law as a separate system that was separate from various other systems in society so as to provide a boundary between the legal system with other systems. The approach method used was the statutory approach; and Conceptual Approach. In principle, the Board of Directors was not personally responsible for acts committed for and on behalf of the company based on its authority. The scope of conduct that would be personally accounted for by the directors of the company was negligence because the directors did not fulfill the contents of the agreement and mistakes because the directors commit acts against the law. Bankruptcy of a Limited Liability Company was the bankruptcy of itself, not the bankruptcy of its management, even though the bankruptcy was due to the negligence of its management. So that management should not be held liable jointly for any losses due to negligence and could only be held accountable if the company's assets were not sufficient to cover losses due to bankruptcy Article 90 paragraph (2) of the Limited Liability Company Law).